Effect of the Magnetospheric Plasma Interaction and Solar Illumination on Ion Sputtering of Europa's Surface Ice. Issue 2 (7th February 2022) - Addison, Peter; Liuzzo, Lucas; Simon, Sven
Abstract: For the entire ion energy range observed at Europa, we calculate spatially resolved maps of the surface sputtering rates of H2 O, O2, and H2 from impacts by magnetospheric ions. We use the perturbed electromagnetic fields from a hybrid model of Europa's plasma interaction, along with a particle‐tracing tool, to calculate the trajectories of magnetospheric ions impinging onto the surface and their resultant sputtering yields. We examine how the distribution of the sputtering rates depends on the electromagnetic field perturbations, the angle between the solar radiation and the corotating plasma flow, and the thickness of the oxygen‐bearing layer within Europa's surface. Our major findings are: (a) Magnetic field‐line draping partially diverts the impinging ions around Europa, reducing the sputtering rates on the upstream hemisphere, but allowing for substantial sputtering from the downstream hemisphere. In contrast, zero sputtering occurs in much of the downstream hemisphere with uniform electromagnetic fields. (b) If the oxygen‐bearing surface layer is thin compared to the penetration depth of magnetospheric ions, thermal ions dominate the O2 sputtering rates, and the region of strongest sputtering is persistently located near the upstream apex. However, if the oxygen‐bearing layer is thick compared to the penetration depth, energetic ions sputter the most O2, and the location of maximum sputtering follows the sub‐solar point as Europa orbits Jupiter. (c) The global production rate of O2 from Europa's surface varies by a factor of 3 depending upon the Moon's orbital position, with the maximum particle release occurring when Europa's Sun‐lit and upstream hemispheres coincide. Key Points: Magnetic field‐line draping partially protects Europa's upstream hemisphere from ion erosion, but causes substantial sputtering downstream If Europa's oxygen‐bearing surface layer is thin compared to the ion penetration depth, maximum sputtering occurs near the upstream apex For a thick oxygen‐bearing layer, two oxygen sputtering maxima form: one near the sub‐solar point, and a weaker one near the upstream apex